Overview of evidence-based clinical practice guidelines for difficult airway management in adults: a systematic review - Ciapponi, Agustín (2021)
Background : The aim of the clinical practice guidelines (CPGs) in the management of difficult airway is to provide optimal responses to a potentially life-threatening clinical problem.Objective : to summarize and compare relevant recommendations and algorithms from evidence-based CPGs (EB-CPGs).Methods : We conducted a systematic review (overview) of CPGs, following Cochrane methods. We summarized recommendations, its supporting evidence and strength of recommendations according to the GRADE methodology. In July 2018, we searched CPGs that were published in the last 10 years, without language restrictions, in electronic databases, and searched specific CPG sources, reference lists and consulted experts. We searched PubMed, EMBASE, Cochrane Library, LILACS, Tripdatabase and additional sources. Pairs of independent reviewers selected EB-CPGs and rated their methodological quality using the AGREE-II instrument. We included those EB-CPGs reporting standard methods for identification, data collection, study risk of bias assessment and recommendations’ level of evidence. Discrepancies were solved by consensus.Results: We included 11 EB-CPGs out of 2505 references identified in literature searches within the last ten years. Only three of them used the GRADE system. The domains with better performance in the AGREE-II assessment, were ‘adequate description of scoping’ and ‘objectives’ while those with worst performance were ‘‘Guidelines’ applicability’ and ‘monitoring’. As a result, only three EB-CPGs were classified as ‘Highly recommended, two as ‘Recommended’ and six as ‘Not recommended. We summarized 22 diagnostic recommendations, 22% of which were supported by high/moderate quality of evidence (41% of them were considered by developers as strong recommendations), and 16 therapeutic/preventive recommendations, 59% of which were supported by high/moderate quality of evidence (76% strong). Only half of the EB-CPGs were updated in the past five years.Conclusions : The main EB-CPGs in the management of difficult airway in anesthesia presented significant heterogeneity in terms of their quality and system of grading the evidence and strength of recommendation used, and most used their own systems. We present many strong recommendations that are ready to be considered for implementation, and we reveal opportunities to improve guidelines’ quality.